The Effect of Motivation and Job Satisfaction on Employee Performance at CV. Sengon Maju Lancar Kediri - Deananda, Ersa; Iryanti, Endang (Business and Investment Review, 2025)
This study investigates the influence of motivation and job satisfaction on employee performance at CV. Sengon Maju Lancar, a wood-processing company in Kediri, Indonesia. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 50 production employees through structured questionnaires. The results reveal that motivation has a significant and positive effect on employee performance, with achievement being the most influential motivational factor. In contrast, job satisfaction does not significantly affect performance, suggesting that satisfaction alone may not drive productivity in this context. These findings highlight the importance of motivational strategies in enhancing workforce effectiveness, particularly in labor-intensive industries. The study contributes to the literature by providing empirical evidence from a small and medium-sized enterprise (SME) in Indonesia and offers practical recommendations for human resource management.